Sensory Evolution on the Threshold : Adaptations in Secondarily Aquatic Vertebrates. - Thewissen, J. G. M. (University of California Press, 2008)
Ranging from crocodiles and penguins to seals and whales, this synthesis explores the function and evolution of sensory systems in animals whose ancestors lived on land. It explores the dramatic transformation of smell, taste, sight, hearing, and balance that occurred as lineages of reptiles, birds, and mammals returned to aquatic environments.